The Existence of The Eits Chaim Jewish Community in Jakarta - Yopi Burhanudin; Subhan Agung; Randi Muchariman (International Journal of Social Sciences Review, 2021)
This study is titled The Existence of Eits Chaim Jewish Community in Jakarta. This research is motivated by the presence of Jews in Indonesia, which is long enough and is motivated by a lack of research sources that discuss the issue of the Jewish nation and their religion, Judaism. This research has a problem restriction that explains the existence of Jews in Jakarta and how the football of the Eits Chaim community. The basis of the theory used is the theory of multiculturalism. This research uses qualitative-case study methods. The location of this study is in the city of Jakarta. Based on the results of research that the Eits Chaim community is a community or organization that aims to accommodate people of Iraqi, Peruvian, and Dutch Jewish descent scattered throughout Indonesia and help those who want to convert to Judaism which is their ancestral religion. Eits Chaim did not spread Judaism because Judaism itself is a religion of descent, but if any non-Jews want to follow the teachings of Judaism, it is permissible.